A Sunless Sea : A William Monk Novel - Perry, Anne (New York : Ballantine Books, 2012)
Monk discovers a shocking truth while investigating the murder of a high-end prostitute with ties to an opium-dispensing doctor's widow.
Keywords: Monk, William (Fictional character) -- Fiction; Detectives -- Fiction -- London (England); Homicide -- Fiction; London (England) -- Fiction -- History -- 19th century; Mystery fiction